The mode of action of recombinant Mycobacterium tuberculosis shikimate kinase: kinetics and thermodynamics analyses. - Leonardo Astolfi Rosado; Igor Bordin Vasconcelos; Mário Sérgio Palma; Vincent Frappier; Rafael Josef Najmanovich; Diógenes Santiago Santos; Luiz Augusto Basso (PLoS ONE, 2013)
Tuberculosis remains as one of the main cause of mortality worldwide due to a single infectious agent, Mycobacterium tuberculosis. The aroK-encoded M. tuberculosis Shikimate Kinase (MtSK), shown to be essential for survival of bacilli, catalyzes the phosphoryl transfer from ATP to the carbon-3 hydroxyl group of shikimate (SKH), yielding shikimate-3-phosphate and ADP. Here we present purification to homogeneity, and oligomeric state determination of recombinant MtSK. Biochemical and biophysical data suggest that the chemical reaction catalyzed by monomeric MtSK follows a rapid-equilibrium random order of substrate binding, and ordered product release. Isothermal titration calorimetry (ITC) for binding of ligands to MtSK provided thermodynamic signatures of non-covalent interactions to each process. A comparison of steady-state kinetics parameters and equilibrium dissociation constant value determined by ITC showed that ATP binding does not increase the affinity of MtSK for SKH. We suggest that MtSK would more appropriately be described as an aroL-encoded type II shikimate kinase. Our manuscript also gives thermodynamic description of SKH binding to MtSK and data for the number of protons exchanged during this bimolecular interaction. The negative value for the change in constant pressure heat capacity (ΔCp) and molecular homology model building suggest a pronounced contribution of desolvation of non-polar groups upon binary complex formation. Thermodynamic parameters were deconvoluted into hydrophobic and vibrational contributions upon MtSK:SKH binary complex formation. Data for the number of protons exchanged during this bimolecular interaction are interpreted in light of a structural model to try to propose the likely amino acid side chains that are the proton donors to bulk solvent following MtSK:SKH complex formation.